Symbrachydactyly - Balakrishnan, Govindasamy; Vijayaragavan, S.; Somesh, Balakrishnan (Indian Journal of Plastic Surgery, 2021)
Symbrachydactyly is a rare congenital hand malformation in which a child is born with abnormally short digits that may be webbed, misshaped, or missing, and it is usually a unilateral condition. There is no standardized treatment algorithm for the management of symbrachydactyly. The function of the hand is often not adequate and requires early surgical intervention to restore useful prehension and appearance. This CME article presents a brief review of the embryology, history, classification and clinical presentation, and author's experience of treating 19 children with symbrachydactyly over 10 years. Creation of thumb web, lengthening of thumb, and creating an opposition post results in prehension of hand with an improved quality of life.
Keywords: congenital hand; symbrachydactyly; free phalangeal transfer; toe transfer; Poland syndrome; thumb web release; square flap